2015
DOI: 10.1111/pce.12661
|View full text |Cite
|
Sign up to set email alerts
|

The key regulator of submergence tolerance, SUB1A, promotes photosynthetic and metabolic recovery from submergence damage in rice leaves

Abstract: The submergence-tolerance regulator, SUBMERGENCE1A (SUB1A), of rice (Oryza sativa L.) modulates gene regulation, metabolism and elongation growth during submergence. Its benefits continue during desubmergence through protection from reactive oxygen species and dehydration, but there is limited understanding of SUB1A's role in physiological recovery from the stress. Here, we investigated the contribution of SUB1A to desubmergence recovery using the two near-isogenic lines, submergence-sensitive M202 and toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 75 publications
(162 reference statements)
3
68
2
Order By: Relevance
“…SUB1A constitutively promoted a phosphoenolpyruvate carboxylase mRNA (OS09G0315700; OsPPC2b ) and regulated the decline during recovery of another (OS01G0208700; OsPPC4 ). These data support the conclusion that photosynthetic recovery is more rapid in M202(Sub1) following submergence, as demonstrated through direct monitoring by Alpuerto et al (). Despite this recovery, M202(Sub1) appears to continue restricting starch catabolism during the early period of recovery.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…SUB1A constitutively promoted a phosphoenolpyruvate carboxylase mRNA (OS09G0315700; OsPPC2b ) and regulated the decline during recovery of another (OS01G0208700; OsPPC4 ). These data support the conclusion that photosynthetic recovery is more rapid in M202(Sub1) following submergence, as demonstrated through direct monitoring by Alpuerto et al (). Despite this recovery, M202(Sub1) appears to continue restricting starch catabolism during the early period of recovery.…”
Section: Resultssupporting
confidence: 88%
“…SUB1A improves reoxygenation tolerance and physiological recovery compared to submergence‐intolerant plants, and it partially ameliorates the dehydration response (Fukao et al, ). A recent study linked the more rapid photosynthetic recovery in SUB1A ‐containing plants with higher photosystem II electron transport efficiency (Alpuerto, Hussain, & Fukao, ).…”
Section: Introductionmentioning
confidence: 99%
“…In both cultivars phytol increase coincided with chlorophyll a decline in the youngest fully expanded leaf (Figure c) by days 5 (Frument) and 12 (Jackson). MDA is considered a useful indicator of lipid peroxidation (Hodges, DeLong, Forney, & Prange, ), as measured using thiobarbituric acid‐reactive substances for assessing oxidative stress in wheat and rice during submergence or hypoxia (Albrecht & Wiedenroth, ; Alpuerto et al, ; Li et al, ). In our study, ANOVA showed significant time, cultivar, and interaction effects for shoot MDA (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Shorter cutting height limited these stress responses, but we still observed significant elevations in the amino acid, nitrate, and ammonium contents as compared to its counterpart (20°C – 2.5 cm treatment). Free amino acids are known to accumulate during heat and other abiotic stresses such as drought and flooding for membrane stabilization, free radical scavenging, and osmotic adjustment (Rai, 2002; Seki et al, 2007; Du et al, 2011; Rutledge et al, 2012; Tamang et al, 2014; Alpuerto et al, 2016). An increase in amino acid content in stubble would be an acclimation response to the stress.…”
Section: Discussionmentioning
confidence: 99%
“…After centrifugation, 300 μL of the supernatant was neutralized with 75 μL of 1 M bicin (pH 8.3) and 70 μL of 4 M potassium hydroxide. Following centrifugation, the supernatant was used for nitrate, ammonium, and amino acid assays as described in van Veen et al (2013) and Alpuerto et al (2016). For nitrate, the extract (10 μL) was incubated with 40 μL of 5% (w/v) salicylic acid in 100% sulfuric acid at 25°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%